Fabrication of Artificial Bioreceptor for Chloramphenicol Detec htion Based on Molecularly Imprinted Polymer Technique - Phi, Van Toan; Nguyen, Quoc Hao; Truong, Thi Ngoc Lien (Old Journal, 2018)
In this paper we present our research on the development of impedimetric sensor for Chloramphenicol (CAP) detection by using artificial bioreceptor MIP. Our results show that fabricated sensor has high selectivity and low detection limit (LOD = 3,67 nM). Furthermore, the process for sensor fabrication has low cost as cheap screen-printed carbon ink electrode but possesses many advantages of possibility for using Au-printed electrode, simple measurement method, short fabrication time and good reproducibility.